Experimental investigation of circumferentially non-uniform heat flux on the heat transfer coefficient in a smooth horizontal tube with buoyancy driven secondary flow - Dirker, Jaco (University of Pretoria, 2018)
Dissertation (MEng)--University of Pretoria, 2018.